Real estate in the digital era. (April 2019) - Harris, Rob
This article describes the relationship between economic and technological change and the design and management of contemporary workplaces. The article describes the changing nature of workstyles resulting from economic and technological change which are driving new business models. General management is increasingly having to address the nature of the workplace in order to attract and retain skilled and expensive workers.